A safe and efficacious Pt(ii) anticancer prodrug: design, synthesis, in vitro efficacy, the role of carrier ligands and in vivo tumour growth inhibition. Issue 12 (9th January 2019) - Dutta, Pradip Kumar; Sharma, Rupali; Kumari, Smita; Dubey, Ravindra Dhar; Sarkar, Sujit; Paulraj, Justin; Vijaykumar, Gonela; Pandey, Manoj; Sravanti, L.; Samarla, Mallik; Das, Hari Sankar; Yashpal,; et al.
Abstract : A new Pt(ii ) prodrug, developed by a combined drug development approach. Abstract : Diaminocyclohexane-Pt(ii )-phenalenyl complexes (1 and2 ) showed an appropriate balance between efficacy and toxicity. Compound2 showed nearly two-fold higher tumour growth inhibition than oxaliplatin in a murine NSCLC tumour model, when a combined drug development approach was used. The fluorescent properties of phenalenone were utilized to understand the mechanistic details of the drug.